Secondhand Smoke Exposure in Hospitality Venues in Europe - Lopez, Maria J. (National Institute of Environmental Health Sciences, 2008)
BACKGROUND: Although in the last few years some European countries have implemented smoking bans in hospitality venues, the levels of secondhand smoke (SHS) in this occupational sector could still be extremely high in most countries. OBJECTIVE: The aim of this study was to assess exposure to SHS in hospitality venues in 10 European cities. METHODS: We included 167 hospitality venues (58 discotheques and pubs, 82 restaurants and cafeterias, and 27 fast-food restaurants) in this cross-sectional study. We carried out fieldwork in 10 European cities: Vienna (Austria), Paris (France), Athens (Greece), Florence and Belluno (Italy), Galway (Ireland), Barcelona (Spain), Warsaw and Lublin (Poland), and Bratislava (Slovak Republic). We measured vapor-phase nicotine as an SHS marker. RESULTS: We analyzed 504 samples and found nicotine in most samples (97.4%). We found the highest median concentrations in discos/pubs [32.99 μg/m(3); interquartile range (IQR), 8.06–66.84 μg/m(3)] and lower median concentrations in restaurants/cafeterias (2.09 μg/m(3); IQR, 0.49–6.73 μg/m(3)) and fast-food restaurants (0.31 μg/m(3); IQR, 0.11–1.30 μg/m(3)) (p < 0.05). We found differences of exposure between countries that may be related to their smoking regulations. Where we sampled smoking and nonsmoking areas, nicotine concentrations were significantly lower in nonsmoking areas. CONCLUSIONS: Hospitality venues from European cities without smoking regulations have very high levels of SHS exposure. Monitoring of SHS on a regular basis as well as a total smoking ban in hospitality sector would be needed.